Analysis of data on breastfeeding in Croatia from 2005 to 2016 - Maja Miloš; Urelija Rodin; Duška Tješić-Drinković; Aida Mujkić (Medicinski glasnik, 2019)
Aim: To analyse available breastfeeding data in Croatia and to describe the process of gathering, collecting, recording and reporting on them to the official institutions. Methods: Infant nutrition data collected at maternity wards and infant nutrition data from primary health care units during the period 2005 to 2016 have been used. Descriptive statistics was used to analyse the data and to show the trends in breastfeeding. Results: More than 85% of newborns were exclusively breastfed in the maternity wards. Data on breastfeeding from primary health care showed growth in exclusive breastfeeding up to 2011, followed by a fall in 2013. From 2012, paediatric teams had the obligation to join information system (CEZIH), but electronic forms did not contain infant nutrition information. Similarly in the E-Newborn project (E-novorođenče) the question on the feeding method in the application was not designated as mandatory. Conclusion: The routinely collected data on breastfeeding did not allow us to draw any conclusion regarding breastfeeding trends in Croatia. In order to improve the process of gathering, recording and reporting data on breastfeeding to the proper authorities, it would be necessary to clearly align definitions, employ a uniform methodology, and upgrade the computer applications in primary health-care. Only then may the reports required for compulsory health insurance be obtained via the CEZIH, as well as the public health reports necessary to monitor preventive work in care of children's health, and monitoring public health indicators.
Keywords: data collection; feeding methods; infant nutrition; primary health care